Application of Synthesised Zeolite A from Kankara Kaolin for Solar Adsorption Refrigeration - Amber, Ityona; Folayan, Clement O.; Suleiman, Rekiyah B. O.; Atta, Abdulazeez Yusuf (Asian Journal of Engineering and Applied Technology, 2013)
This paper presents the synthesis, characterization and application of a synthesised Zeolite A from Nigerian clay (kankara) for application in solar adsorption refrigeration.On the basis of X-ray diffraction, TGA and DTA experiments Zeolite A was confirmed with and adsorption capacity of 0.3 kg adsorbate / 0.85kg adsorbent, regenerative temperature of below 2000C and structural stability below 8000C. The refrigeration system used in the test consists of a 0.6 by 0.45 m2 parabolic trough concentrator, 0.6m long and 0.25m diameter black coated absorber, an air cooled condenser and cooling box of volume(evaporator) 0.048m3. The refrigerator was constructed and tested at the Mechanical Engineering Department Zaria, Nigeria at location 11.11’NE in the month of April, a month with one of the highest of average solar irradiation of 900W/m2. The lowest evaporator temperature attained was 9.80C with a C.O.P of 28.5%.